A new deep-sea squat lobster (Decapoda: Anomura) from a seamount of the Arabian Sea, India, with re-description of Gonionida comorina (Alcock & Anderson, 1899) - Tiwari, Shivam; Padate, Vinay P.; Cubelio, Sherine Sonia (Zootaxa, 2026)
A new species of the deep-sea squat lobster genus Munidopsis Whiteaves, 1874, is described from a seamount in the southeastern Arabian Sea, India. Munidopsis hindmahasagarae sp. nov. differs from its close congeners, M. alcocki Ahyong, 2014 and M. treis Ahyong & Poore, 2004 by the presence of a tooth on the distomesial margin of the antennule, a relatively longer distolateral tooth of the second antennal article, and a relatively longer distomesial tooth of the third antennal article. Gonionida comorina (Alcock & Anderson, 1899) is redescribed and illustrated based on fresh material, as well as comparison with photographs and the description of the type specimen. Its re-description enables confirmation of its placement in the genus Gonionida Macpherson & Baba, 2022, owing to a triangular fourth thoracic sternite. Juveniles of Eumunida sp. are compared with congeners from the western Indian Ocean namely, E. funambulus Gordon, 1930, E. similior Baba, 1990, and E. spiridonovi Macpherson, Rodríguez-Flores & Machordom, 2017.